2014
DOI: 10.12955/emhpj.v7i1.428
|View full text |Cite
|
Sign up to set email alerts
|

Effectivenes of Spironolacton in Complex Therapy of Rheumatoid Arthritis

Abstract: Aldosterone blocker – Spironolactone has anti-inflammatory, anti-proliferative and anti-oxidative effects, that is why pathogenetically it is expedient to use it in complex therapy of rheumatoid arthritis.Material and methods: 46 patients with RA took 25-50 mg/day of Spironolactone during 12 months as an addition to standard therapy, the comparison group consisted of 47 patients that got only standard therapy, all the patients were fully examined prior and post the treatment.Results: complex RA therapy leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Komarova and Rebrov [ 11 ] followed patients with RA for 12 months while they were on additional therapy of 25–50 mg/day of spironolactone and observed a significant reduction in DAS28 value ( p -value = 0.048) and also found improvement in the VAS and HAQ (Health Assessment Questionnaire), suggesting improvement in patients’ quality of life. It concluded that spironolactone contributes to more pronounced improvement in indices along with reduction of anti-inflammatory, anti-proliferative and angiogenic cytokines and more effectively reduces disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Komarova and Rebrov [ 11 ] followed patients with RA for 12 months while they were on additional therapy of 25–50 mg/day of spironolactone and observed a significant reduction in DAS28 value ( p -value = 0.048) and also found improvement in the VAS and HAQ (Health Assessment Questionnaire), suggesting improvement in patients’ quality of life. It concluded that spironolactone contributes to more pronounced improvement in indices along with reduction of anti-inflammatory, anti-proliferative and angiogenic cytokines and more effectively reduces disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Spironolactone is a steroid that blocks mainly the effects of the hormone aldosterone but also its antiinflammatory anti-proliferative and anti-oxidant effects are described. However, few studies have shown the effectiveness of spironolactone in therapy of rheumatoid arthritis [ 11 , 13 ]. This is because it blocks aldosterone, which possesses proinflammatory and profibrotic properties, due to its stimulating action on cytokines, molecules of adhesion and different growth factors [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation